2021
DOI: 10.3390/cryst11040329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of the Influence of RDX Internal Defects on Sensitivity

Abstract: The internal defect is an important factor that could influence the energy and safety properties of energetic materials. RDX samples of two qualities were characterized and simulated to reveal the influence of different defects on sensitivity. The internal defects were characterized with optical microscopy, Raman spectroscopy and microfocus X-ray computed tomography technology. The results show that high-density RDX has fewer defects and a more uniform distribution. Based on the characterization results, defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The existence of defects may affect the stability of the crystal. 5,20 The vacancy formation energy (E f ) is often used to evaluate the stability of these systems. In addition, the vacancy binding energy (E b ) 21 can be introduced to describe the change of the system energy of the formation of double-vacancy and triple-vacancy systems by the single-vacancy system, in order to explore the differences in vacancy formation energy between these systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of defects may affect the stability of the crystal. 5,20 The vacancy formation energy (E f ) is often used to evaluate the stability of these systems. In addition, the vacancy binding energy (E b ) 21 can be introduced to describe the change of the system energy of the formation of double-vacancy and triple-vacancy systems by the single-vacancy system, in order to explore the differences in vacancy formation energy between these systems.…”
Section: Resultsmentioning
confidence: 99%
“…The vicinity of the void was more prone to the formation of reaction centers, where explosive molecules within these reaction centers were more likely to undergo decomposition. Yan et al 5 discovered that the existence of vacancy defects decreases the cohesion energy density (CED) and increases the maximum bond lengths ( L max ) of N–NO 2 for 1,3,5-trinitro-1,3,5-triazine (RDX) crystals through molecular dynamics (MD) simulations, suggesting that the presence of defects enhances the sensitivity of the RDX crystals. In addition, they observed that a higher defect concentration and a more uneven distribution of the defects lead to the higher sensitivity of RDX.…”
Section: Introductionmentioning
confidence: 99%
“…However, the crystal growth process may be affected by disturbance from external factors, which leads to the presence of defects in the explosive crystals [5][6][7]. The presence of crystal defects can affect the performance of explosives, such as stability, susceptibility and energy characteristics, which further affects the safety and operational performance of weapons and munitions [8,9]. Therefore, studying the effects of crystal defects on the performance of explosives is of great theoretical and practical importance.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, it is necessary to study the internal defects of explosives. Yan et al 8 established vacancy defect models with different defect densities and found that the model with the lowest defect density exhibited the shortest initiation bonds and the highest cohesive energy density. Miao et al 9 used molecular dynamics simulations to investigate the influence of doping defects on the performance of polymer-bonded explosives (PBXs).…”
Section: Introductionmentioning
confidence: 99%